Duty of loyalty and due care of the board member under Polish law - Pinior, Piotr (Review of European and Comparative Law, 2022)
Duty of loyalty and due care of the board’s members have been lately introduced to the provisions of the Polish Commercial Companies Code. This paper aims to define the duty of loyalty and due care of the board members, as presented in the Polish doctrine, as well as in the British, Spanish, and German laws. Additionally, the impact of the new provisions on the liability of the board members shall be described.